On influence of structural features on stress-strain state of a reinforced concrete floor slab - A. V. Selivanov; F. F. Reger; I. A. Chakurin (Вестник СибАДИ, 2022)
Introduction. An assessment of the influence for the type of bonds and the magnitude of the prestress of the longitudinal working reinforcement on the stress-strain state of the reinforced concrete floor slab, developed by the authors was made.Materials and methods. The studies on a finite element model of a reinforced concrete floor slab, implemented in LIRA software package were carried out.Results. The development of stress values and transverse vertical displacements directly depended on the support conditions of the floor slab.Limitation of transverse horizontal displacements on the support by any of the selected methods made it possible to reduce stresses by 3.47 - 3.78 times, deflections by 1.5 - 1.52 times, stresses - up to 11.9 times, wребро deflections - 1.18–1.53 times.Creating an end rib or limiting movement with an additional horizontal connection had almost the same effect.The transverse horizontal displacements of the lower face of the longitudinal contour rib in the direction of the 𝑢ребро span which occurred in the floor slab, which did not have an end rib and limitation of displacements in the transverse direction, were in a parabolic relationship with the magnitudes of the vertical transverse forces.In a florr slab with limited displacements in the transverse direction or with an end rib, 𝑢ребро displacements were 3.88–4.32 times less, and at the ends they depended on the deformability of the bonds, i.e. when horizontal movement was prohibited, they were equal to zero. stresses acting on the lower edge of the flange in the transverse direction, in the region of the middle of the span in the floor slab with reinforcement prestressed to the maximum value, had positive values almost over the entire width of the flange and directly depended on the thickness of the slab in each section.Prestressing made it possible to reduce deflections by 4.02 - 4.37 times, wребро deflections by 1.09 - 5.59 times, and evenly distribute stresses along the length of the longitudinal contour rib, to make they are only tensile, close to zero along its entire length.The prestressing of the reinforcement of the maximum value made it possible to increase the horizontal rigidity of the longitudinal contour rib of the floor slab and limit its transverse 𝑢ребро movements.The transverse displacements that occurred near the support of the prestressed shell slab were 1.04 - 1.2 times less than in the shell slab with non-stressed reinforcement, on the rest of the span - slightly more, changing evenly, without sharp changes, unlike floor slabs with non-stressed reinforcement.Discussion and conclusion. It is established that the optimal design of the floor slab under the study should have restrictions on the movements of the supports and the maximum possible prestressing of the longitudinal working reinforcement.The practical significance of the study is that the specified reference conditions and prestress allow maximum deformation resistance of the structure, which in our case directly affects the bearing capacity of the slab.